Exploring Sleep Hygiene Practices during the Covid-19 Pandemic in Children and Adolescents: A Scoping Review - Leona, Vivi Amelia; Chung, Min-Huey; Bojang, Pa Ousman; Chang, Pi-Chen (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: Amidst the Covid-19 Pandemic, school closures and social distancing measures have introduced challenges that may contribute to sleep issues in children and adolescents. Delving into the exploration of sleep hygiene practices becomes crucial for a comprehensive understanding of these practices during this unique period. Purpose: This scoping review aims to comprehensively synthesize existing literature on how the Covid-19 pandemic has influenced the sleep behavior, encompassing aspects like physical activity, screen time, and substance use among children and adolescents aged 5-19 years. Methods: The extensive literature searches across five databases (Ebsco, Pubmed, Science Direct, Scopus, and Google Scholar). Out of the 1278 references initially identified, a meticulous screening process led to the inclusion of 41 eligible studies for thorough analysis. Results: Among the 41 studies analyzed, 29 focused on physical activity, 14 explored screen time, and 10 delved into substance use. Notably, a majority of participants exhibited a reduction in sleep duration during lockdown. Physical activity was primarily impacted by a decrease in its duration, and recommended interventions for increasing physical activity included home-based, online-based, and mixed interventions. The majority of participants experienced an increase in screen time, engaging in academic and leisure activities. Interestingly, substance use behaviors declined amidst the pandemic situation. Conclusion: Sleep hygiene behaviors have undergone notable changes during the pandemic, particularly in terms of reduced physical activity and increased screen time. On a positive note, there has been a reported decline in substance use behaviors. The pivotal role of parents emerges as crucial in fostering positive behaviors among children and adolescents during these challenging times.